International cooperation to improve access to and sustain effectiveness of antimicrobials. Issue 10015 (16th January 2016) - Årdal, Christine; Outterson, Kevin; Hoffman, Steven J; Ghafur, Abdul; Sharland, Mike; Ranganathan, Nisha; Smith, Richard; Zorzet, Anna; Cohn, Jennifer; Pittet, Didier; Daulaire, Nils; Morel, Chantal; et al.
Summary: Securing access to effective antimicrobials is one of the greatest challenges today. Until now, efforts to address this issue have been isolated and uncoordinated, with little focus on sustainable and international solutions. Global collective action is necessary to improve access to life-saving antimicrobials, conserving them, and ensuring continued innovation. Access, conservation, and innovation are beneficial when achieved independently, but much more effective and sustainable if implemented in concert within and across countries. WHO alone will not be able to drive these actions. It will require a multisector response (including the health, agriculture, and veterinary sectors), global coordination, and financing mechanisms with sufficient mandates, authority, resources, and power. Fortunately, securing access to effective antimicrobials has finally gained a place on the global political agenda, and we call on policy makers to develop, endorse, and finance new global institutional arrangements that can ensure robust implementation and bold collective action.